Analysis of the Results of the Pedagogical Research and Eeg in the Aspect of Effective Modern Teaching Aids in the Technical Education - Prauzner, Tomasz (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The development of computer technology is reflected in among other things, the development of modern didactics. Current pedagogy and media education, as a fast developing discipline of general pedagogy, is a topic of a number of studies. Applying the modern multimedia aids at various stages and in various types of education is considered as an indispensable element of modern didactics, due to new opportunities the modern media offers. The paper deals with didactic innovations based on research conducted within pedagogy on the observable social changes induced by development in information technology. The main objective of the paper is to address the issue how to apply modern technology and research findings on the functioning of the brain in order to improve the effectiveness of the learning process. The paper presents only the results of a pilot study, which can be used as a basis for further research using medical equipment for analyzing EEG brain waves for didactic purposes.